Funktsional'naya model' sportsmena-orientirovshchika na osnove individual'nykh znachenii anaerobnogo poroga - Borilkevich, V. E.; Zorin, A. I.; Mikhaylov, B. A.; Lomova, I. A. (Teorija i Praktika fiziceskoj Kul'tury, 1999)
The functional model of the athlete-orienteer based on the individual values of anaerobic threshold (AnT) is offered. The AnT was measured by the noninvasive method according the data of cardiorespiratory indices. The level of physical preparadness was defined by results of 3000 m race for females and 5000 m race for males, as well as by the results of orienteering competitions. The model can be used for the correction of training process and for the selection of the best athletes into the combined teams of various level.